Sistem sensor untuk pemantauan kadar oksigen terlarut berbasis galvanik pada kolam budidaya ikan air tawar - Damar Wicaksono; Tatag Lindu Bhakti; Restiadi Bayu Taruno; Melvin Rahma Sayuga Subroto; Anita Mustikasari (Jurnal Teknologi dan Sistem Komputer, 2021)
This study aims to develop low-cost and environmentally friendly material galvanic-based dissolved oxygen sensors. A Dissolved oxygen (DO) sensor has been designed and fabricated on an 85 x 205 mm galvanic-based. The sensor structure device consists of Al-Zn reference layer electrode, Ag/AgCl active electrode, 120ml KCl electrolyte solvent 0,1 M, and closed by TiO2 membrane (PTFE). The Al-Zn formation reference electrode was done by Ag layer chlorination using FeCl3, and the TiO2 membrane was formed by TiO2 paste screen printing. The test was done to measure the sensor’s performance based on the current-voltage characteristics between 1.0 and 1.8 V. The results showed that a stable diffusion current was obtained when the input voltage was 1.5 V, resulting in the best sensor performance with a sensitivity of 0.7866 μA L/mg and a stable step response time of 3 mins. This prototype sensor showed high potential for prototyping for a low-cost water quality monitoring system.